IMPLEMENTATION OF KURIKULUM MERDEKA IN INTEGRATED ISLAMIC SCHOOL - Yuli Marlina; Teti Muliawati; Mohamad Erihadiana (Balai Diklat Keagamaan Bandung, 2023)
Indonesian education continues to develop to produce a competitive and morally upright generation. As a process, the administration of Kurikulum Merdeka continues to be developed with an independent learning curriculum as its guiding principle. In addition, it is anticipated that learning will be student-centered by prioritizing children's overall growth and development and by encouraging teachers to always be student-centered. This research seeks to collect field-based information on the implementation of Kurikulum Merdeka in Islamic senior high schools. The descriptive qualitative method with Rogers' theory of diffusion innovation was used, and data analysis was conducted through interviews and direct observations with the school dean and 27 instructors. The findings of this study indicate that the Kurikulum Merdeka not only offers new learning experiences to teachers but is also capable of unifying divisions in the learning process with results derived from both the innovation attribute and innovation development process. The subsequent research is an evaluation of the curriculum that has been implemented in Senior High Schools or Islamic Senior High Schools.Keywords: Islamic Education; Kurikulum Merdeka; Integrated Islamic School